2017
DOI: 10.1073/pnas.1700477114
|View full text |Cite
|
Sign up to set email alerts
|

Microglial NFκB-TNFα hyperactivation induces obsessive–compulsive behavior in mouse models of progranulin-deficient frontotemporal dementia

Abstract: Frontotemporal dementia (FTD) is the second most common dementia before 65 years of age. Haploinsufficiency in the progranulin (GRN) gene accounts for 10% of all cases of familial FTD. GRN mutation carriers have an increased risk of autoimmune disorders, accompanied by elevated levels of tissue necrosis factor (TNF) α. We examined behavioral alterations related to obsessive-compulsive disorder (OCD) and the role of TNFα and related signaling pathways in FTD patients with GRN mutations and in mice lacking progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 48 publications
6
109
0
Order By: Relevance
“…Treatment with 1 lM PF, a PYK2 inhibitor, or 3 lM U0126, a MEK/ERK inhibitor, largely prevented Ab 42 -induced microglial activation (Figure 8a,b). As introduced above, it has been welldocumented that TNF-a is potent in inducing neurotoxicity and that Ab-induced generation of TNF-a from microglial cells significantly contributes to neuroinflammation in AD (Alam et al, 2016;Block et al, 2007;Doll et al, 2015;Heppner et al, 2015;Krabbe et al, 2017;Liu & Hong, 2003;Montgomery et al, 2011;Montgomery et al, 2013;Wyss-Coray & Rogers, 2012). Treatment with 1 lM PF or 3 lM U0126 strongly inhibited Ab 42 -induced activation of PARP-1 (Figure 9a It has been well recognized that Ab causes neuroinflammation via inducing microglial activation and generation of excessive proinflammatory cytokines, thereby contributing to AD (Heneka et al, 2015;Heppner et al, 2015).…”
Section: Ab 42 Activates the Trpm2 Channel Via Promoting Generationmentioning
confidence: 88%
See 1 more Smart Citation
“…Treatment with 1 lM PF, a PYK2 inhibitor, or 3 lM U0126, a MEK/ERK inhibitor, largely prevented Ab 42 -induced microglial activation (Figure 8a,b). As introduced above, it has been welldocumented that TNF-a is potent in inducing neurotoxicity and that Ab-induced generation of TNF-a from microglial cells significantly contributes to neuroinflammation in AD (Alam et al, 2016;Block et al, 2007;Doll et al, 2015;Heppner et al, 2015;Krabbe et al, 2017;Liu & Hong, 2003;Montgomery et al, 2011;Montgomery et al, 2013;Wyss-Coray & Rogers, 2012). Treatment with 1 lM PF or 3 lM U0126 strongly inhibited Ab 42 -induced activation of PARP-1 (Figure 9a It has been well recognized that Ab causes neuroinflammation via inducing microglial activation and generation of excessive proinflammatory cytokines, thereby contributing to AD (Heneka et al, 2015;Heppner et al, 2015).…”
Section: Ab 42 Activates the Trpm2 Channel Via Promoting Generationmentioning
confidence: 88%
“…(g) Summary of TNF-a release determined by ELISA from microglial cells after exposed to Ab 42 at indicated concentrations for 72 hr from four independent cell preparations. TNF-a is a major neurotoxic cytokine generated by microglial cells (Block, Zecca, & Hong, 2007;Doll, Rellick, Barr, Ren, & Simpkins, 2015;Heppner et al, 2015;Krabbe et al, 2017;Sedger & McDermott, 2014). *p < .05; **p < .01; ***p < .005 compared with control [Color figure can be viewed at wileyonlinelibrary.com] ALAWIEYAH SYED MORTADZA ET AL.…”
mentioning
confidence: 99%
“…Several studies in mouse suggest that microglia may directly affect behavior. For example, absence of homeobox protein Hox‐B8 (Hoxb8) or progranulin in microglia leads to obsessive–compulsive disorder (OCD)‐like symptoms in rodents, such as excessive grooming , while absence of Cx3cr1 leads to ASD‐like symptoms . A recent study also observed a sex‐specific role for microglial phagocytosis in male social play , setting the stage for further study of molecular mechanisms by which microglia cause psychiatric symptoms.…”
Section: Tissue‐resident Immunity Of the Brain: Cellular Playersmentioning
confidence: 99%
“…Heterozygous Grn knockout mice also present with milder social deficits, but still include reduced sociability . Homozygous knockout mice also show marked gliosis and inflammatory markers in the brain, and interfering with inflammatory pathways rescues several behavioural impairments and improves survival in these mice . Depending on the extent of knockdown (and potentially other factors), selective knockdown of progranulin in microglia is also sufficient to induce social grooming impairments and compulsive behaviour in mice .…”
Section: Genetic Models Of Ftdmentioning
confidence: 99%
“…Homozygous knockout mice also show marked gliosis and inflammatory markers in the brain, and interfering with inflammatory pathways rescues several behavioural impairments and improves survival in these mice . Depending on the extent of knockdown (and potentially other factors), selective knockdown of progranulin in microglia is also sufficient to induce social grooming impairments and compulsive behaviour in mice . However, behavioural abnormalities in heterozygous Grn knockout mice and neuronal‐specific knockout occur without concomitant microgliosis or neuroinflammation , suggesting that they are not essential for the development of these phenotypes.…”
Section: Genetic Models Of Ftdmentioning
confidence: 99%